UPAYA MENINGKATKAN HASIL BELAJAR PENDIDIKAN AGAMA ISLAM MELALUI PENERAPAN METODE PEMBELAJARAN DEMONSTRASI DI KELAS VII-1 SMP NEGERI 2 BINJAI KAB. LANGKAT - Halimatussa’diah Halimatussa’diah (PGSD Universitas Negeri Medan, 2018)
The purpose of this study was to determine the increase in Islamic education learning outcomes on the subject of plural prayer and Qashar through the application of demonstration learning methods in class VII-1 of Binjai District 2 Middle School. Langkat. This research design is a Class Action Research using the Kemmis and Taggart research model, which is spiral from one cycle to the next. The results of this study are: 1) In Cycle I the implementation of the learning model Demonstrations obtained student learning outcomes from 26 students obtained 19 people who completed 73.1% and 7 people who did not complete with 26.9%. 2) In the second cycle student learning outcomes from 26 students were obtained 23 people who completed 88.5% and 3 people who did not complete with 11.5%. From the findings of this study it can be concluded that the application of demonstration learning methods can improve the learning outcomes and skills of plural prayers and qasar of class VII-1 students of SMP Negeri 2 Binjai, Kab. Langkat.Keywords: Learning Model, Demonstration, PAI